Home-school relations : working successfully with parents and families - Fuller, Mary Lou.; Olsen, Glenn (Boston : Allyn and Bacon, 1998)
This book is about: Families and their functions; Diversity among families; Teachers and parenting; Parents in the school; ...
Keywords: Education; Home and school -- United States -- Case studies; Parent-teacher relationships -- United States -- Case studies; Education, Primary -- Parent participation -- United States -- Case studies; Early childhood education -- Parent participation -- United States -- Case studies